THU0257 ESTIMATED 10-YEARS CARDIOVASCULAR RISK IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS: PRELIMINARY RESULTS FROM THE "CARDIOVASCULAR OBESITY AND RHEUMATIC DISEASE (CORDIS)" STUDY GROUP OF THE ITALIAN SOCIETY OF RHEUMATOLOGY. (2nd June 2020) - Cacciapaglia, F.; Manfredi, A.; Erre, G.; Bartoloni Bocci, E.; Sakellariou, G.; Viapiana, O.; Colella, S.; Abbruzzese, A.; Fornaro, M.; Cafaro, G.; Fenu, M. A.; Palermo, B. L.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) patients are at high risk for CV events, and EULAR recommends assessing the 10-year CV-risk using the Systematic Coronary Risk Evaluation (SCORE) [1]. The QRISK3, another score to assess CV-risk in UK population, considers different factors among which also SLE. The Progetto Cuore score (PCS) is validated to estimate CV risk in Italian people and largely replicates the SCORE project [2]. Objectives: This cross-sectional study aimed to estimate CV-risk using SCORE, QRISK3 and, for the first time, PCS in a multicentric cohort of Italian SLE patients. Methods: During 2019 we evaluated 173 SLE patients (87.7% female; age 40±16 years; disease duration 138±105 months), fulfilling the 1997 ACR classification criteria. Clinical and laboratory data were registered, and individual CV-risk was calculated using suitable algorithms for the SCORE, QRISK3 and PCS. Statistical analysis was performed using Graphpad Instat 8.0 (San Diego, CA-USA). Results: In 13 (7%) SLE patients a previous CV event was recorded. Hypertension was present in 60 (37.5%) and diabetes in 27 (16.9%) patients. Mean total cholesterol was 184±39 mg/dL, HDLc 58±18 mg/dL, LDLc 124±37 mg/dL, triglycerides 105±63 mg/dL; dyslipidaemia was reported in 58 (36.2%) patients and 29 (18.1%) were on statin. Mean BMI was 24.9±5.3 Kg/sm, 60 (37.5%) and 23 (14.3%) patients were overweight and obese, while 25 (15.6%) patients were smokers. 87 (54.3%) SLE patients had a SLEDAI<4, 91% of patients were taken HCQ and 65% were on prednisone (mean dose 5.4±5.9 mg/day), but only 7.5% took >7.5 mg/day. The CV-risk of SLE patients according to SCORE, QRISK3 and PCS was 1.1±2.1%, 10.5±12.3% and 3.7±5.4%, respectively. Stratifying patients at low, moderate or high CV risk according to the PCS and SCORE a double proportion of patients was at moderate (8% vs 3.9%) or high (1.9% vs 0.9%) CV risk (p=0.03). Finally, CV-risk according to QRISK3 was higher than 20% (high risk) in 32/160 (20%) patients. Conclusion: This multicentre study demonstrated that the mean estimated CV-risk in SLE patients is globally low using the SCORE, QRISK3 and PCS. The PCS seems to better intercept those patients at moderate/high risk, at least in Italian SLE patients, while QRISK3 predicts the highest CV risk. The lack of disease-specific CV-risk factors (such as autoantibodies profile or organ involvement) probably account for the underestimation of CV risk using the SCORE and PCS. References: [1]ARD 2019;78(6):736-745. [2]ARD 2019;0:1–2. doi: 10.1136/annrheumdis-2019-215715 Disclosure of Interests: Fabio Cacciapaglia Speakers bureau: BMS; Roche; Pfizer; Abbvie, Andreina Manfredi: None declared, Gianluca Erre: None declared, Elena Bartoloni Bocci: None declared, Garifallia Sakellariou Speakers bureau: Abbvie, Novartis, MSD, Ombretta Viapiana: None declared, Sergio Colella: None declared, Anna Abbruzzese: None declared, Marco Fornaro: None declared, Giacomo Cafaro: None declared, Maria Antonietta Fenu: None declared, Bianca Lucia Palermo: None declared, Martina Dessì: None declared, Adalgisa Palermo: None declared, Alessandro Giollo: None declared, Elisa Gremese Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Sanofi, UCB, Roche, Pfizer, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Sanofi, UCB, Roche, Pfizer, Francesca Romana Spinelli Grant/research support from: Pfizer, Speakers bureau: Lilly, BMS, Celgene, Fabiola Atzeni: None declared, Matteo Piga: None declared